Studying the Contribution of Serotonin to Neurodevelopmental Disorders. Can This Fly? - Carvajal-Oliveros, Angel; Campusano, Jorge M. (Frontiers in Behavioral Neuroscience, 2021)
Serotonin is a biogenic amine that acts as neurotransmitter in different brain regions and is involved in complex behaviors, such as aggression or mood regulation. Thus, this amine is found in defined circuits and activates specific receptors in different target regions. Serotonin actions depend on extracellular levels of this amine, which are regulated by its synthetic enzymes and the plasma membrane transporter, SERT. Serotonin acts also as a neurotrophic signal in ontogeny and in the mature brain, controlling cell proliferation, differentiation, neurogenesis and neural plasticity. Interestingly, early alterations in serotonergic signaling have been linked to a diversity of neurodevelopmental disorders, including Autism Spectrum Disorder (ASD), attention deficit/hyperactivity disorder (ADHD), or mental illnesses like schizophrenia or depression. It has been proposed that given the complex and numerous actions of serotonin, animal models could better serve to study the complexity of serotonin actions, while providing insights on how hindering serotonergic signaling could contribute to brain disorders. In this mini-review it will be examined what the general properties of serotonin acting as a neurotransmitter in animals are, and furthermore, whether it is possible that Drosophila could be used to study the contribution of this amine to neurodevelopmental and mental disorders